How to steal a dog : a novel - O'Connor, Barbara (New York : Farrar, Straus & Giroux, 2007)
Living in the family car in their small North Carolina town after their father leaves them virtually penniless, Georgina, desperate to improve their situation and unwilling to accept her overworked mother's calls for patience, persuades her younger brother to help her in an elaborate scheme to get money by stealing a dog and then claiming the reward that the owners are bound to offer.
"Frances Foster books."
700
S
Keywords: Homeless persons -- Fiction; Family problems -- Fiction; Conduct of life -- Fiction; Interpersonal relations -- Fiction; Siblings -- Fiction; Dogs -- Fiction; North Carolina -- Fiction